Titanium-free anti-ultraviolet mica material as well as preparation method and application thereof

By using a multi-layer coating process on the mica substrate, an ultraviolet shielding layer, a sealing layer, a hydrophobic layer and an ultraviolet absorption layer are formed, which solves the problem of insufficient long-wave ultraviolet shielding ability and carcinogenic risk of existing mica titanium pearlescent pigments, and achieves efficient ultraviolet shielding and good hydrophobicity.

CN119868186APending Publication Date: 2025-04-25LUZHAI SEVEN-COLOR PEARLESCENT MICA MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510138707.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing mica titanium pearlescent pigments may accelerate skin aging after absorbing ultraviolet rays, and nanotitanium dioxide has a risk of carcinogenicity and has weak shielding ability to long-wave ultraviolet rays.

Method used

By coupling the inorganic oxides with organic matter, a multi-layer coating process is used to coat the surface of the mica substrate with different functions, forming a four-layer coating structure: an ultraviolet shielding layer, a sealing layer, a hydrophobic layer and an ultraviolet absorbing layer.

Benefits of technology

Effective shielding of ultraviolet rays with wavelengths of 280~400nm is achieved, with low UV transmittance, high SPF value, and good hydrophobicity, avoiding the risk of skin aging and carcinogenicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119868186A_ABST
    Figure CN119868186A_ABST
Patent Text Reader

Abstract

The invention discloses a titanium-free anti-ultraviolet mica material as well as a preparation method and application thereof. The titanium-free anti-ultraviolet mica material comprises a mica base material, an ultraviolet shielding layer coated on the surface of the base material, a sealing layer coated on the surface of the ultraviolet shielding layer, an optional hydrophobic layer coated on the surface of the sealing layer, and an ultraviolet absorption layer coated on the outermost layer. The preparation method comprises the following steps: coupling an inorganic oxide and an organic matter, and coating substances with different effects on the surface of a mica base material layer by layer through a multi-layer coating process, so as to obtain the mica material for cosmetics, which has multiple effects of ultraviolet shielding, ultraviolet absorption, dispersion and hydrophobicity and the like. And when being used in cosmetics, the anti-aging composition does not accelerate skin aging, is not carcinogenic, has an excellent shielding effect on ultraviolet rays, and has relatively high SPF value, low ultraviolet transmittance and relatively good hydrophobicity. In addition, the technological process is simple and easy to operate, raw materials are easy to obtain, and the method has good conditions and basis for large-scale industrial popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a functional mica material, in particular to a titanium-free UV-proof mica material and a preparation method and application thereof, belonging to the technical field of functional mica materials. Background Art

[0002] Mica pearlescent pigments, with their unique optical properties and color effects, shine in the field of cosmetics and personal care products, such as lip gloss, eye shadow, powder, nail polish, body lotion, face cream, shampoo, conditioner, etc. The main function is to keep the skin in good condition by beautifying, cleaning or protecting it, so as to avoid dry skin or damage by ultraviolet rays, thereby maintaining skin health.

[0003] Synthetic fluorphlogopite powder is often used to make cosmetics, but it has no obvious shielding effect on ultraviolet rays, has a low SPF value and high ultraviolet transmittance. Therefore, researchers have proposed a mica titanium pearlescent pigment (i.e., titanium dioxide coated on the surface of mica). Although mica titanium pearlescent pigment can shield ultraviolet rays, it also has many problems: First, nano titanium dioxide TiO2 can shield ultraviolet rays, but according to the latest research, nano-scale titanium dioxide is very easy to produce oxygen free radicals after absorbing ultraviolet rays, which will accelerate skin aging. Second, nano titanium dioxide can also trigger photocatalytic oxidation reactions, causing other ingredients in cosmetics to denature. Third, nano titanium dioxide is a carcinogen and has been included in the regulatory catalog by major economies such as the European Union and North America. Fourth, nano titanium dioxide has a strong shielding ability for medium-wave ultraviolet (UVB) in the 280~320nm band, but has a weak shielding ability for long-wave ultraviolet (UVA) in the 320~400nm band, and long-wave ultraviolet can penetrate the dermis and is the culprit for suntan and skin cancer. As people pay more attention to skin health, the demand for UVA protection in cosmetics is gradually increasing. Summary of the invention

[0004] In view of the problems in the prior art that the existing mica titanium pearlescent pigments will accelerate skin aging, have weak long-wave ultraviolet shielding ability and are carcinogenic, the present invention provides a titanium-free UV-proof mica material, which couples inorganic oxides with organic matter, and wraps substances with different functions layer by layer on the surface of the mica substrate through a multi-layer coating process, thereby obtaining a mica material for cosmetics that has multiple functions such as UV shielding, UV absorption, dispersion and hydrophobicity.

[0005] According to a first embodiment of the present invention, a titanium-free UV-resistant mica material is provided: A titanium-free UV-proof mica material comprises a mica substrate, a UV shielding layer coated on the surface of the substrate, a sealing layer coated on the surface of the UV shielding layer, a hydrophobic layer optionally coated on the surface of the sealing layer, and a UV absorbing layer coated on the outermost layer.

[0006] The ultraviolet shielding layer is an oxide layer composed of one or more of zinc oxide, zirconium oxide, silicon dioxide, and magnesium oxide (preferably zirconium oxide and / or zinc oxide).

[0007] The sealing layer is an oxide layer composed of one or both of aluminum oxide and cerium oxide (preferably cerium oxide).

[0008] The hydrophobic layer is an organic silane layer.

[0009] The ultraviolet absorption layer is an organic layer composed of aromatic compounds containing carbonyl groups and having a conjugated structure.

[0010] It should be noted that in the present invention, "optionally" means "with" or "without". The "optionally a hydrophobic layer coated on the surface of the sealing layer" means that the surface of the sealing layer may be coated with a hydrophobic layer or not, and the selection is adjusted according to actual needs.

[0011] Preferably, the aromatic compound containing a carbonyl group and having a conjugated structure is selected from the group consisting of butyl methoxydibenzoylmethane (CAS: 70356-09-1), bis-ethylhexyloxyphenol methoxyphenyl triazine (CAS: 187393-00-6), polysilicone-15 (CAS: 207574-74-1), 2-cyano-3,3-diphenylacrylate-2-ethylhexyl ester (CAS: 6197-30-4), 4-methoxycinnamic acid ethylhexyl ester (CAS: 5466-77-3), 2-hydroxy-4-methoxybenzophenone (CAS: 131-57-7), salicylic acid-2-ethylhexyl ester (CAS: 118-60-5) or one or more thereof.

[0012] Preferably, the organosilane is one or more of dimethiconol (CAS: 31692-79-2), n-octyltriethoxysilane (CAS: 2943-75-1), aminopropyltriethoxysilane (CAS: 919-30-2), stearic acid (CAS: 57-11-4), palmitic acid (CAS: 57-10-3), myristic acid (CAS: 544-63-8), preferably one or more of aminopropyltriethoxysilane, stearic acid, and n-octyltriethoxysilane.

[0013] Preferably, the mica substrate is synthetic fluorphlogopite and / or natural mica, and has a particle size of 1-15 μm, preferably 3-8 μm, and a thickness of 200-350 nm, preferably 250-300 nm.

[0014] Preferably, the thickness of the ultraviolet shielding layer is such that its mass is 1-50% of the total mass of the finished material, preferably 10-40%, and more preferably 20-36%.

[0015] Preferably, the sealing layer has a thickness such that its mass is 0.1-2%, preferably 0.2-1.8%, and more preferably 0.3-1.5% of the total mass of the finished material.

[0016] Preferably, the hydrophobic layer has a thickness such that its mass is 0-5%, preferably 0.4-4%, and more preferably 0.6-3.5% of the total mass of the finished material.

[0017] Preferably, the thickness of the ultraviolet absorption layer is such that its mass is 0.3-10% of the total mass of the finished material, preferably 0.5-9%, and more preferably 0.8-8%.

[0018] It should be noted that, during the coating process of each coating layer (UV shielding layer, sealing layer, hydrophobic layer, UV absorption layer, etc.), the final mass proportion of the obtained coating layer can be adjusted by adjusting the time of each coating reaction, and the final mass proportion of the obtained coating layer can also be adjusted by adjusting the mass concentration of the coating liquid during coating.

[0019] In the present invention, the titanium-free UV-proof mica material of the present invention has a four-layer coating structure, with a core of sheet mica (such as synthetic fluorphlogopite mica) as a substrate (average thickness of 200-350 nm, average particle size of 1-15 μm), and is coated with a UV shielding layer, a sealing layer, an optional hydrophobic layer and a UV absorption layer in sequence. Among them: (1) UV shielding layer: a layer of oxide coated on the surface of the mica substrate, which uses the UV scattering effect of the oxide crystals to play a role in UV shielding, belonging to physical protection. The main component of the UV shielding layer is a mixture of one or more of zinc oxide (ZnO), zirconium oxide (ZrO2), silicon dioxide (SiO2), magnesium oxide (MgO), etc. (the mixing method can be to dope two or more of the above oxides in a uniform layer, or to subdivide the UV shielding layer into multiple layers, each layer is a single type of the above oxide). Its coating mass accounts for 1-50% of the total mass of the product (preferably 10-40%, more preferably 20-36%). (2) Sealing layer: A layer of oxide coated on the surface of the ultraviolet shielding layer, the main purpose of which is to close the surface of the ultraviolet shielding layer, prevent cation dissolution, fill lattice defects, isolate zinc oxide, zirconium oxide, etc. from the cosmetic system, and prevent them from undergoing photocatalytic oxidation reaction under ultraviolet radiation. The main components of the sealing layer are one of aluminum oxide Al2O3 and rare earth cerium oxide CeO2, etc., and a mixture of the two (the mixing method is the same as above). Its coating mass accounts for 0.1-2% of the total mass of the product (preferably 0.2-1.8%, more preferably 0.3-1.5%). It should be noted that when the coverage rate of the ultraviolet shielding layer is reduced, the coverage rate of the sealing layer also needs to be reduced accordingly (even when the coverage rate of the ultraviolet shielding layer is low enough, the sealing layer can be eliminated, that is, a hydrophobic layer or ultraviolet absorption layer is directly coated on the surface of the ultraviolet shielding layer. This situation should be regarded as a special case within the scope of protection claimed by the present invention). Generally, the thickness of the sealing layer does not exceed 20% (preferably 15%) of the thickness of the ultraviolet shielding layer. (3) Hydrophobic layer: Since the materials of the first two layers and the synthetic fluorphlogopite itself are hydrophilic surfaces, and cosmetics are mostly oily or oil-water emulsion systems, the powder needs to have good hydrophobicity and dispersibility. The hydrophobic layer is formed by coating the surface of the powder with organic molecules containing aliphatic hydrocarbon groups at one end to improve its hydrophobicity and dispersibility. The organic matter used for surface modification can be a mixture of one or more of polydimethylsiloxane, n-octyl triethoxysilane, aminopropyl triethoxysilane, stearic acid, palmitic acid, myristic acid, etc. (the mixing method is the same as above). The coating mass of the ultraviolet absorption layer accounts for 0-5% of the total mass of the product (preferably 0.4-4%, more preferably 0.6-3.5%). (4) Ultraviolet absorption layer: The main component of this layer is ultraviolet absorbers, which are a class of aromatic compounds containing carbonyl groups and having conjugated structures (a mixture of one or more alone, the mixing method is the same as above), which can absorb ultraviolet rays and convert them into molecular vibration or other forms of harmless energy. Its principle belongs to chemical protection.The UV absorption layer and the UV shielding layer cooperate and complement each other to greatly improve the sunscreen effect of the product. The coating mass of the UV absorption layer accounts for 0.3-10% (preferably 0.5-9%, more preferably 0.8-8%) of the total mass of the product. In addition, since each UV absorber has a specific absorption band, the effect of using several absorbers in combination is better.

[0020] In the existing technology, nano zinc oxide can replace nano titanium dioxide in some cases, but zinc oxide is not acid- and alkali-resistant and cannot be used in certain cosmetic systems. 2+ Ions react with the cosmetic system to form fatty acid zinc, resulting in gelation, a sharp increase in viscosity, and sunscreens and sprays cannot be made. In addition, nano zinc oxide has a large specific surface area and high surface energy. It is easy to agglomerate when used alone and has poor dispersibility. On the other hand, the ultraviolet shielding performance of nano zinc oxide is lower than that of nano titanium dioxide. Ultraviolet absorbers are usually hydrophilic organic molecules that are difficult to disperse in cosmetics. The sunscreen produced is prone to recrystallization when applied, which is what consumers often call the "mud rubbing" phenomenon, resulting in reduced sunscreen function. The titanium-free ultraviolet mica material of the present invention has the property of shielding ultraviolet rays with a wavelength of 280~400nm through the special structure and the selective coupling of the coating layer, specifically including: (1) ultraviolet transmittance <5%; (2) sun protection index SPF value >50. In addition, the titanium-free ultraviolet mica material has surface hydrophobicity, specifically a water contact angle >120°.

[0021] According to a second embodiment of the present invention, a method for preparing a titanium-free UV-resistant mica material is provided: A method for preparing a titanium-free UV-proof mica material or a method for preparing a titanium-free UV-proof mica material as described in the first embodiment, the method comprising the following steps: 1) Dispersing a mica substrate in water to obtain a mica suspension, heating the mica suspension, adding a solution containing ultraviolet shielding agent ions thereto and stirring the suspension for reaction, and after the reaction is completed, calcining the fixed product to obtain product A.

[0022] 2) Product A is dispersed in water to obtain suspension A. After the suspension A is heated, a solution containing blocking agent ions is added thereto and stirred for reaction. After the reaction is completed, the fixed product obtained is product B.

[0023] 3) Product B is placed in a container, and then a solution containing a hydrophobic agent is added and mixed evenly to obtain a mixture, the mixture is heated to perform a curing reaction and the solvent is completely volatilized, and product C is obtained after the reaction is completed.

[0024] 4) dispersing the product B or product C in a solution containing an ultraviolet absorber to obtain a suspension C, concentrating the suspension C and performing low-temperature and reduced-pressure drying treatment to obtain a titanium-free ultraviolet-resistant mica material.

[0025] Preferably, in step 1), the solution containing the UV shielding agent ions is Zn 2+ 、Zr 4+ 、SiO3 2- Mg 2+ The salt solution of one or more of the above is preferably a salt solution containing zinc chloride, zinc nitrate, zinc sulfate, zirconium tetrachloride, zirconium sulfate, sodium silicate, potassium silicate, sodium metasilicate, potassium metasilicate, magnesium chloride, and magnesium sulfate. Preferably, the concentration of the solution containing the ultraviolet shielding agent ions is 0.5-2 mol / L. The amount added is adjusted according to the target coating thickness.

[0026] Preferably, in step 1), the solid mass concentration in the mica suspension is 5-15%, preferably 8-12%.

[0027] Preferably, in step 1), heating the mica suspension is specifically: heating the mica suspension to 50-75° C., preferably 55-70° C. Preferably, the pH during the stirring reaction is controlled to be 6.5-7.5, preferably 6.8-7.2.

[0028] Preferably, in step 1), the calcination temperature is 500-1200° C., preferably 600-750° C. The calcination time is 0.1-3 h, preferably 0.3-2 h.

[0029] Preferably, in step 2), the solution containing the blocking agent ions is Al 3+ and / or Ce 4+ The salt solution is preferably a salt solution containing one or more of aluminum chloride, aluminum nitrate, aluminum sulfate, and cerium nitrate. Preferably, the concentration of the solution containing the blocking agent ions is 0.5-1 mol / L. The amount added is adjusted according to the target coating thickness.

[0030] Preferably, in step 2), the solid mass concentration in the suspension A is 5-12%, preferably 7-10%.

[0031] Preferably, in step 2), heating the suspension A specifically comprises: heating the mica suspension to 60-90° C., preferably 70-85° C. Preferably, after heating, the pH of the suspension A is controlled to be 6-8, preferably 6.5-7.5.

[0032] Preferably, in step 3), the solution containing the hydrophobic agent is an organic solution containing one or more of polydimethylsiloxane, n-octyl triethoxysilane, aminopropyl triethoxysilane, stearic acid, palmitic acid, and myristic acid. The organic solvent is one or more of ethyl acetate, ethanol, water, citric acid, acetic acid, oxalic acid, and hydrochloric acid. Preferably, the mass concentration of the solution containing the hydrophobic agent is 5 to 50%, preferably 8 to 45%.

[0033] Preferably, in step 3), the solution containing the hydrophobic agent is added by atomization spraying, and the amount added is adjusted according to the target coating thickness, and is generally required to be added within 15 minutes.

[0034] Preferably, in step 3), the mixture is heated for reaction by heating the mixture to 100-140° C. and baking for 4-12 h, preferably heating the mixture to 110-135° C. and baking for 5-10 h, under stirring.

[0035] Preferably, in step 4), the solution containing the ultraviolet absorber is an organic solution containing one or more of butyl methoxydibenzoylmethane (CAS: 70356-09-1), bis-ethylhexyloxyphenol methoxyphenyl triazine (CAS: 187393-00-6), polysilicone-15 (CAS: 207574-74-1), 2-cyano-3,3-diphenylacrylate-2-ethylhexyl ester (CAS: 6197-30-4), 4-methoxycinnamic acid ethylhexyl ester (CAS: 5466-77-3), 2-hydroxy-4-methoxybenzophenone (CAS: 131-57-7), and salicylic acid-2-ethylhexyl ester (CAS: 118-60-5). The organic solvent is one or more of petroleum ether, ethyl acetate, ethanol, isopropanol, and water. Preferably, the mass concentration of the solution containing the ultraviolet absorber is 0-10%, preferably 0-2%.

[0036] Preferably, in step 4), the solid-liquid mass ratio of the intermediate product B or the intermediate product C to the solution containing the ultraviolet absorber is 1:4-12, preferably 1:6-10. Preferably, in step 4), the suspension C is concentrated and dried at low temperature and reduced pressure by first heating the suspension C to 40-60°C under vacuum conditions for evaporation concentration (preferably heating to 45-55°C for evaporation concentration) and continuing to heat under reduced pressure until the solvent is completely volatilized.

[0037] In the present invention, the ultraviolet shielding layer is the first oxide layer (including ZnO, ZrO2, SiO2, MgO, etc.) coated on the outside of the mica substrate. The method for making the ultraviolet shielding layer is mainly chemical liquid deposition, the principle of which is to add the target salt solution to the mica suspension at a constant temperature, pH value, and feeding rate in a uniformly stirred mica powder suspension, and neutralize it with acid or alkali to keep the pH constant. The metal ions (silicon element is silicate) are hydrolyzed to form hydrated intermediates and settle on the surface of the mica substrate under the action of electrostatic adsorption. Subsequently, a dense coating layer is obtained by filtration, washing, and calcination. The main reaction formulas include: ZnCl2 + 2NaOH == Zn(OH)2 + H2O + 2NaCl hydrolysis precipitation; Zn(OH)2 == ZnO + H2O↑ Calcination; ZrOCl2 + 2NaOH == ZrO·2H2O + 2NaCl hydrolysis deposition; ZrO·2H2O == ZrO2 + 2H2O↑ Calcination; Na2SiO3 + 2HCl == H2SiO3 + 2NaCl hydrolysis precipitation; H2SiO3 == SiO2 + H2O↑ Calcination.

[0038] The coating process of the ultraviolet shielding layer is as follows: firstly, the synthetic fluorphlogopite powder is dispersed in pure water to obtain a mica suspension with a solid mass concentration of 5-15% (preferably 8-12%); then, the mica suspension is heated to 50-75°C (preferably 65-70°C) and the temperature is maintained constant; then, a solution containing ultraviolet shielding agent ions (specifically, containing Zn 2+ 、Zr 4+ Mg 2+A salt solution of metal cations, such as zinc chloride, zinc nitrate, zinc sulfate, zirconium tetrachloride, zirconium sulfate, magnesium chloride, magnesium sulfate, etc., is dissolved in a dilute hydrochloric acid solution (e.g., a hydrochloric acid solution with a mass fraction of about 5-10%) to obtain a metal salt solution with a concentration of 0.5-2 mol / L. When the coating material is SiO2, a soluble silicate is used, such as sodium silicate, potassium silicate, sodium metasilicate, potassium metasilicate, etc., dissolved in pure water to obtain a silicate solution with a concentration of 0.5-1 mol / L, and then the silicate solution is added to the mica suspension at a constant speed, and the pH value is maintained at 8-10 by neutralization with dilute hydrochloric acid while adding the materials. After the addition is completed, the reaction continues for a period of time (e.g., 30min-60min). When the coating material is a metal oxide such as ZnO2, ZrO2, MgO, etc., the salt solution of the metal cation is added to the mica suspension at a constant rate, and the acid produced by the hydrolysis of the metal salt is neutralized with an alkaline solution (which can be a sodium hydroxide solution, a calcium hydroxide solution, a lime milk, a calcium carbonate suspension, etc.) while adding the material, so that the pH value is maintained at 5~7. After the addition is completed, the reaction continues for a period of time (for example, 30min~60min). Finally, the suspension after the reaction is filtered, and the obtained solid is washed and dried to a constant weight; finally, the dried powder is placed in a high-temperature furnace and calcined at a temperature of 500~2000℃ (preferably 600~750℃) for 0.1~3h (preferably 0.3~2h) to obtain a mica material coated with a UV shielding layer (hereinafter referred to as product A).

[0039] In the present invention, the sealing layer is a second oxide layer (including Al2O3 and / or CeO2) coated on the outside of the mica substrate. The method for making the sealing layer is to disperse the calcined product A in water, and deposit the metal ion hydrate on the mica surface by hydrolysis of aluminum salt and cerium salt, and then filter, dry and calcine for the second time. The specific coating process is as follows: first disperse the product A in pure water to obtain a suspension A with a solid mass concentration of 5-12% (preferably 7-10%); then heat the suspension A to 60-90°C (preferably 70-85°C) and maintain a constant temperature, adjust the pH of the suspension A to 5.5-7 (preferably 5.8-6.5); then add a solution containing sealing agent ions (specifically containing Al 3+ , and / or Ce 4+ A salt solution of a metal cation, such as a metal salt such as aluminum chloride, aluminum nitrate, aluminum sulfate, or cerium nitrate dissolved in pure water to obtain a metal salt solution with a concentration of 0.5 to 1 mol / L, is added to the suspension A at a constant rate. After the addition is completed, the reaction is continued with stirring for a certain period of time (e.g., 30 to 60 minutes). After the reaction is completed, the obtained suspension is filtered, and the obtained filter cake is washed and dried to a constant weight to obtain the product B.

[0040] In the present invention, the hydrophobic layer is a third layer of material (mainly silane containing aliphatic hydrocarbon groups or fluorine-substituted aliphatic hydrocarbon groups) coated on the outside of the mica substrate. There are two process methods for making the hydrophobic layer: (1) coating the hydrophobic layer alone, specifically comprising the following steps: firstly loading the product B into a mixer, and then spraying a pre-prepared solution containing a hydrophobic agent into the mixer in an atomized manner (specifically, dissolving the hydrophobic agent in a pre-prepared solvent, the solvent being a composite of one or more of ethyl acetate, ethanol, water, citric acid, acetic acid, oxalic acid, and hydrochloric acid, for example, the composite solvent is 0-5wt% of water, 68-94.5wt% of a mixture of ethyl acetate and ethanol, and 0.5-2wt% of an acid (preferably hydrochloric acid or acetic acid); specifically, adding the hydrophobic agent to the solvent and stirring the mixture to obtain a solution with a mass concentration of 5 ~25wt% (preferably 8~20%) of hydrophobic agent solution), controlling the stirring speed of the mixer to 300~2000rpm to fully mix the powder and the solution containing the hydrophobic agent to obtain a mixture; then baking the mixture at 100~140°C (preferably 100~120°C) for 4~12h (preferably 5~10h); finally, adding the baked powder to an air flow disperser, specifically at a feeding rate of 3~5kg / min and an air flow pressure of 0.5~0.75Mpa, collecting the product C with a cyclone separator, and then performing the outermost layer coating.

[0041] (2) The hydrophobic layer and the ultraviolet absorption layer are prepared simultaneously. The specific steps are as follows: dissolving the hydrophobic agent and the ultraviolet absorber in the solution at the same time, adding a dilute acid with a mass concentration of 0-0.5% (the amount added is 0.5-2% of the mass of the solution) to obtain a mixed solution. First, disperse the product B in the mixed solution and continue stirring to obtain a suspension. The mass ratio of the mixed solution to the product B is 4-12:1 (preferably 6-10:1); then heat the mixed suspension to 40-60°C (preferably 45-55°C) under vacuum conditions to evaporate the solution, recover the evaporated fraction through a condenser, and finally load the evaporated powder into a high-speed disperser and disperse it at 500-2000rpm for 1-5 minutes to obtain the final product. That is, the ultraviolet absorber is added at the same time as the hydrophobic modification is completed by coating, eliminating the step of separate coating, and the effect of the obtained product is equivalent.

[0042] It should be noted that in certain specific cases, it is necessary to maintain the hydrophilicity of the mica material (such as making foundation liquid, sunscreen products, etc.), and in this case, it is not necessary to make a hydrophobic layer (that is, directly coating the UV absorption layer on the surface of the sealing layer). This situation should be regarded as a special case within the scope of protection claimed by the present invention.

[0043] In the present invention, the ultraviolet absorption layer is a substance (mainly an aromatic compound containing a carbonyl group and having a conjugated structure) coated on the outermost layer of the mica substrate. The method for making the ultraviolet absorption layer is to disperse the product C coated with a hydrophobic layer (or the product B without a hydrophobic layer) in an organic solvent, using one of ethanol, ethyl acetate, isopropanol or petroleum ether, or mixing the above-mentioned solvents in a certain proportion according to the polarity of the organic molecules to be dissolved. The mica solution is mixed with the pre-configured ultraviolet absorber solution under negative pressure and heating conditions, and the solution is refluxed until it is nearly dry and then taken out and dried at low temperature, so that the ultraviolet absorber can be coated on the surface of the product C (or product B). The specific coating process is as follows: first, disperse the product C (or product B) in a solution containing an ultraviolet absorber (specifically, an organic solution of an ultraviolet absorber. The solvent is a composite of one or more of petroleum ether, ethyl acetate, ethanol, isopropanol, and water, for example, the composite solvent is 0-5wt% water, 5-95wt% of a mixture of petroleum ether, ethyl acetate, ethanol, and isopropanol, and 0-0.5wt% of an acid (hydrochloric acid); the mass concentration of the ultraviolet absorber is 0-10wt%, preferably 0-2%) and continuously stir to obtain a suspension, wherein the mass ratio of the solution to the solid is 4-12:1 (preferably 6-10:1); then, heat the suspension to 40-60°C (preferably 45-55°C) under vacuum conditions to evaporate the solution, recover the evaporated fraction through a condenser, and finally, load the evaporated powder into a high-speed disperser and disperse it at a speed of 500-3000 rpm for 1-5 minutes to obtain the final product.

[0044] According to a third embodiment of the present invention, there is provided a use of a titanium-free UV-resistant mica material: A use of a titanium-free UV-proof mica material or the use of the titanium-free UV-proof mica material described in the first embodiment or the use of the titanium-free UV-proof mica material prepared by the method described in the second embodiment, wherein the titanium-free UV-proof mica material is used to prepare cosmetics. Preferably, the titanium-free UV-proof mica material is used to prepare one or more of lip gloss, eye shadow, powder, nail polish, lotion, face cream, shampoo, cleansing cream, and handmade soap.

[0045] In the present invention, absorbance refers to the logarithm of the incident light intensity and the transmitted light intensity of the sample to be tested with base 10. In the application scenario targeted by the present invention, we focus on the absorbance of the product in the 280~400nm band. The absorbance is measured by a UV-visible spectrophotometer and can be measured in the following two forms: ① Disperse the titanium-free UV-resistant mica material product of the present invention in white oil, and measure the UV absorbance of the sample solution at a specified concentration, the commonly used concentration is 30-50%; it is necessary to first measure the absorbance of the blank solution and subtract the background.

[0046] ② Evenly apply the titanium-free UV-resistant mica material product of the present invention on the 3M film, and the coating thickness is controlled at 1.8-2.2 mg / cm 2 , use an SPF meter to measure no less than 9 points and calculate the average value.

[0047] In the present invention, titanium-free UV-proof mica material powder needs to have high compatibility, dispersion stability, and skin affinity with the cosmetic system to achieve the best use effect, and hydrophobicity is the most important evaluation method. The titanium-free UV-proof mica material after surface modification has a solid-liquid interfacial tension formed between it and water that is less than the water-air interfacial tension, and the surface cannot be wetted by water, and has hydrophobic and lipophilic properties. The method for detecting hydrophobicity is to press the product powder into a sample to be tested, drop a certain amount of water on the sample surface, and observe the contact angle of the solid-liquid interface formed by it. The larger the contact angle, the stronger the hydrophobicity. The theoretical range of water contact angle is 0~180°, and the contact angle of the hydrophilic interface is usually <60°. The contact angle of the product described in the present invention is >120°, which is strongly hydrophobic. The contact angle determination method can be static or dynamic, specifically, water drops are dropped on the sample surface with a certain inclination, and the contact angle change of the water droplets when rolling is measured.

[0048] Compared with the prior art, the beneficial technical effects of the present invention are as follows: 1: The titanium-free UV-proof mica material of the present invention does not contain titanium, and will not accelerate skin aging and is not carcinogenic when used in cosmetics. It also has an excellent shielding effect on ultraviolet rays, a high SPF value, low UV transmittance, and good hydrophobicity. The specific performance can be achieved: UV transmittance <5%, SPF value >50, water contact angle >120°.

[0049] 2: The process flow for preparing titanium-free UV-resistant mica material of the present invention is simple, easy to operate, and the raw materials are readily available, and it has good conditions and foundation for large-scale industrial promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is a schematic structural diagram of the titanium-free UV-resistant mica material of the present invention.

[0051] Figure 2 This is a SEM image of the titanium-free UV-resistant mica material prepared in Example 1 of the present invention.

[0052] Reference numerals: 1: mica substrate; 2: UV shielding layer; 3: sealing layer; 4: hydrophobic layer; 5: UV absorbing layer. DETAILED DESCRIPTION

[0053] The technical solution of the present invention is illustrated below by way of example, and the scope of protection requested by the present invention includes but is not limited to the following embodiments. Example 1

[0054] 100 g of synthetic fluorphlogopite powder was dispersed in pure water to obtain a mica suspension with a solid mass concentration of about 10%; the mica suspension was then heated to 65°C and the temperature was maintained constant; then 313 mL of 1.0 mol / L zinc chloride solution (the solvent was a hydrochloric acid solution with a mass fraction of 5%) was added at a uniform rate and the reaction was stirred continuously (while the pH of the reaction was controlled to be 7) for 0.5 h; after the reaction was completed, the mixture was filtered, and the obtained solid was washed and dried to constant weight; finally, the dried powder was placed in a high-temperature furnace and calcined at 550°C for 0.5 h to obtain a mica material coated with a zinc oxide layer (hereinafter referred to as product I).

[0055] Continue to disperse product I in pure water to obtain a suspension I with a solid mass concentration of about 10%; then heat the suspension I to 65°C and maintain a constant temperature, and adjust the pH of the suspension I to 6.5; then add 6mL of 0.5mol / L cerium nitrate solution and continue stirring the reaction for 0.5h; after the reaction is completed, filter, wash the obtained solid and dry it to constant weight to obtain product II.

[0056] Continue to load product II into the mixer, and then spray 12.6 mL of a hydrophobic agent solution with a mass concentration of 40% (containing 8% aminopropyltriethoxysilane, 15% stearic acid, and 17% ethanol mixed solution of n-octyltriethoxysilane) in an atomized manner, the spraying rate is 6 mL / min, and the stirring speed of the mixer is controlled to 550 rpm to fully mix the powder and the hydrophobic agent solution to obtain a mixture; then bake the mixture at 105°C for 8 hours; finally, add the baked powder to an airflow disperser with an airflow pressure of 0.65 MPa at a rate of 4 kg / min and collect it with a cyclone separator to obtain product III.

[0057] The product III is then dispersed in a 10-fold mass of a UV absorber solution (containing 0.1% butyl methoxydibenzoylmethane and 0.2% 2-hydroxy-4-methoxybenzophenone in ethanol) with a concentration of about 0.3%, and the suspension II is continuously stirred; the suspension II is then heated to 60°C under vacuum conditions to evaporate the solvent (the evaporated fraction is recovered by a condenser), and finally the evaporated powder is loaded into a high-speed disperser and dispersed at 1200 rpm for 5 minutes to obtain a titanium-free UV-resistant mica material (referred to as mica material I). According to the test, in mica material I, the coating mass of the UV shielding layer is about 26.2%, the coating mass of the sealing layer is about 0.52%, the coating mass of the hydrophobic layer is about 4.0%, and the coating mass of the UV absorption layer is about 3.3% (all based on the total mass of mica material I); the UV transmittance is about 1.03%, the SPF value is greater than 50, and the water contact angle is about 141°. Example 2

[0058] Example 1 was repeated, except that zinc chloride was replaced by zirconium chloride. After testing, the coating quality of the ultraviolet shielding layer, the sealing layer, the hydrophobic layer, the ultraviolet absorption layer, etc. of the mica material prepared in this example was substantially equivalent to that of the mica material I; its ultraviolet transmittance was about 4.50%, the SPF value was greater than 50, and the water contact angle was about 141°. Example 3

[0059] Example 1 was repeated, except that zinc chloride was replaced by silicon chloride. After testing, the coating quality of the ultraviolet shielding layer, the sealing layer, the hydrophobic layer, the ultraviolet absorption layer, etc. of the mica material prepared in this example was substantially equivalent to that of the mica material I; its ultraviolet transmittance was about 18.52%, the SPF value was about 30, and the water contact angle was about 141°. Example 4

[0060] Example 1 was repeated, except that zinc chloride was replaced by magnesium chloride. After testing, the coating quality of the ultraviolet shielding layer, the sealing layer, the hydrophobic layer, the ultraviolet absorption layer, etc. of the mica material prepared in this example was substantially equivalent to that of the mica material I; its ultraviolet transmittance was about 6.40%, the SPF value was about 44, and the water contact angle was about 141°. Example 5

[0061] Example 1 was repeated, except that the coating reaction time of each coating layer was adjusted with the goal of achieving a coating mass of the UV shielding layer of 32% of the total mass of the finished mica material and keeping the mass proportion of other coating layers unchanged; after testing, in the mica material prepared in this example, the coating mass of the UV shielding layer was approximately 32.5%, the coating mass of the sealing layer was approximately 0.50%, the coating mass of the hydrophobic layer was approximately 4.1%, and the coating mass of the UV absorption layer was approximately 3.3%; its UV transmittance was approximately 0.82%, the SPF value was >50, and the water contact angle was approximately 141°. Example 6

[0062] Example 1 was repeated, except that the coating reaction time of each coating layer was adjusted with the goal of achieving a coating mass of the UV shielding layer of 40% of the total mass of the finished mica material and keeping the mass proportion of other coating layers unchanged; after testing, in the mica material prepared in this example, the coating mass of the UV shielding layer was approximately 39.8%, the coating mass of the sealing layer was approximately 0.52%, the coating mass of the hydrophobic layer was approximately 4.2%, and the coating mass of the UV absorption layer was approximately 3.1%; its UV transmittance was approximately 0.76%, the SPF value was >50, and the water contact angle was approximately 141°. Example 7

[0063] Example 1 was repeated, except that the coating reaction time of each coating layer was adjusted with the goal of achieving a coating mass of the UV shielding layer of 20% of the total mass of the finished mica material and keeping the mass proportion of other coating layers unchanged; after testing, in the mica material prepared in this example, the coating mass of the UV shielding layer was approximately 19.7%, the coating mass of the sealing layer was approximately 0.51%, the coating mass of the hydrophobic layer was approximately 4.2%, and the coating mass of the UV absorption layer was approximately 3.2%; its UV transmittance was approximately 4.94%, the SPF value was approximately 49, and the water contact angle was approximately 141°. Example 8

[0064] Example 1 was repeated, except that the coating reaction time of each coating layer was adjusted with the goal of achieving a coating mass of the UV shielding layer of 12% of the total mass of the finished mica material and keeping the mass proportion of other coating layers unchanged; after testing, in the mica material prepared in this example, the coating mass of the UV shielding layer was approximately 12.4%, the coating mass of the sealing layer was approximately 0.53%, the coating mass of the hydrophobic layer was approximately 4.1%, and the coating mass of the UV absorption layer was approximately 3.0%; its UV transmittance was approximately 7.22%, the SPF value was approximately 42, and the water contact angle was approximately 141°. Example 9

[0065] Example 1 was repeated, except that cerium nitrate was replaced by aluminum nitrate. After testing, the coating quality of the ultraviolet shielding layer, sealing layer, hydrophobic layer, ultraviolet absorption layer, etc. of the mica material prepared in this example was basically equivalent to that of mica material I; its ultraviolet transmittance was about 1.00%, the SPF value was greater than 50, and the water contact angle was about 141°. Example 10

[0066] Example 1 was repeated, except that the coating reaction time of each coating layer was adjusted with the goal of achieving a coating mass of the sealing layer of 0.65% of the total mass of the finished mica material and keeping the mass proportion of other coating layers unchanged; after testing, in the mica material prepared in this example, the coating mass of the UV shielding layer was approximately 26.0%, the coating mass of the sealing layer was approximately 0.66%, the coating mass of the hydrophobic layer was approximately 4.1%, and the coating mass of the UV absorption layer was approximately 3.0%; its UV transmittance was approximately 1.03%, the SPF value was >50, and the water contact angle was approximately 141°. Embodiment 11

[0067] Example 1 was repeated, except that the coating reaction time of each coating layer was adjusted with the goal of achieving a coating mass of the sealing layer of 0.30% of the total mass of the finished mica material and keeping the mass proportion of other coating layers unchanged; after testing, in the mica material prepared in this example, the coating mass of the UV shielding layer was approximately 26.3%, the coating mass of the sealing layer was approximately 0.28%, the coating mass of the hydrophobic layer was approximately 4.1%, and the coating mass of the UV absorption layer was approximately 3.1%; its UV transmittance was approximately 1.01%, the SPF value was greater than 50, and the water contact angle was approximately 141°. Example 12

[0068] Example 1 was repeated, except that the hydrophobic agent solution was replaced by an ethanol mixed solution containing 19% stearic acid and 21% n-octyltriethoxysilane instead of an ethanol mixed solution containing 8% aminopropyltriethoxysilane, 15% stearic acid, and 17% n-octyltriethoxysilane. After testing, the coating quality of the ultraviolet shielding layer, the sealing layer, the hydrophobic layer, the ultraviolet absorption layer, etc. of the mica material prepared in this example was basically equivalent to that of the mica material I; its ultraviolet transmittance was about 1.04%, the SPF value was greater than 50, and the water contact angle was about 138°. Embodiment 13

[0069] Example 1 was repeated, except that the hydrophobic agent solution was replaced by an ethanol solution containing 40% of n-octyltriethoxysilane instead of an ethanol solution containing 8% aminopropyltriethoxysilane, 15% stearic acid, and 17% n-octyltriethoxysilane. After testing, the coating quality of the ultraviolet shielding layer, the sealing layer, the hydrophobic layer, the ultraviolet absorption layer, etc. of the mica material prepared in this example was basically equivalent to that of the mica material I; its ultraviolet transmittance was about 1.01%, the SPF value was greater than 50, and the water contact angle was about 132°. Embodiment 14

[0070] Example 1 was repeated, except that the hydrophobic agent solution was replaced by an ethanol mixed solution containing 40% stearic acid instead of an ethanol mixed solution containing 8% aminopropyltriethoxysilane, 15% stearic acid, and 17% n-octyltriethoxysilane. After testing, the coating quality of the ultraviolet shielding layer, the sealing layer, the hydrophobic layer, the ultraviolet absorption layer, etc. of the mica material prepared in this example was basically equivalent to that of the mica material I; its ultraviolet transmittance was about 1.00%, the SPF value was greater than 50, and the water contact angle was about 125°. Embodiment 15

[0071] Example 1 was repeated, except that the coating reaction time of each coating layer was adjusted with the goal of achieving a coating mass of the hydrophobic layer of 6% of the total mass of the finished mica material and keeping the mass proportion of other coating layers unchanged; after testing, in the mica material prepared in this example, the coating mass of the UV shielding layer was approximately 26.1%, the coating mass of the sealing layer was approximately 0.49%, the coating mass of the hydrophobic layer was approximately 5.7%, and the coating mass of the UV absorption layer was approximately 3.1%; its UV transmittance was approximately 1.02%, the SPF value was >50, and the water contact angle was approximately 141°. Example 16

[0072] Example 1 was repeated, except that the coating reaction time of each coating layer was adjusted with the goal of achieving a coating mass of the hydrophobic layer of 2.5% of the total mass of the finished mica material and keeping the mass proportion of other coating layers unchanged; after testing, in the mica material prepared in this example, the coating mass of the UV shielding layer was approximately 26.2%, the coating mass of the sealing layer was approximately 0.51%, the coating mass of the hydrophobic layer was approximately 2.5%, and the coating mass of the UV absorption layer was approximately 3.2%; its UV transmittance was approximately 1.02%, the SPF value was >50, and the water contact angle was approximately 121°. Embodiment 17

[0073] Example 1 was repeated, except that the coating process of the hydrophobic layer was not carried out, and the mass proportion of other coating layers was controlled to remain unchanged, and the coating reaction time of other coating layers was adjusted; after testing, in the mica material prepared in this example, the coating mass of the ultraviolet shielding layer was approximately 26.1%, the coating mass of the sealing layer was approximately 0.50%, the coating mass of the hydrophobic layer was 0%, and the coating mass of the ultraviolet absorption layer was approximately 3.0%; its ultraviolet transmittance was approximately 1.01%, the SPF value was greater than 50, and the water contact angle was approximately 0°. Embodiment 18

[0074] Example 1 was repeated, except that the ultraviolet absorber solution containing 0.1% butyl methoxydibenzoylmethane and 0.2% 2-hydroxy-4-methoxybenzophenone in ethanol was replaced by an ethanol mixed solution containing 0.1% polysilicone-15 and 0.2% bis-ethylhexyloxyphenol methoxyphenyl triazine. After testing, the coating quality of the ultraviolet shielding layer, the sealing layer, the hydrophobic layer, the ultraviolet absorption layer, etc. in the mica material prepared in this example was basically equivalent to that of the mica material I; its ultraviolet transmittance was about 2.10%, the SPF value was greater than 50, and the water contact angle was about 141°. Embodiment 19

[0075] Example 1 was repeated, except that the ultraviolet absorber solution containing 0.1% butyl methoxydibenzoylmethane and 0.2% ethanol mixed solution of 2-hydroxy-4-methoxybenzophenone was replaced by an ethanol mixed solution containing 0.1% 4-methoxycinnamic acid ethylhexyl ester and 0.2% salicylic acid-2-ethylhexyl ester. After testing, the coating quality of the ultraviolet shielding layer, the sealing layer, the hydrophobic layer, the ultraviolet absorption layer, etc. in the mica material prepared in this example was basically equivalent to that of the mica material I; its ultraviolet transmittance was about 4.11%, the SPF value was greater than 50, and the water contact angle was about 141°. Embodiment 20

[0076] Example 1 was repeated, except that the ultraviolet absorber solution containing 0.1% butyl methoxydibenzoylmethane and 0.2% 2-hydroxy-4-methoxybenzophenone in ethanol was replaced with an ethanol solution containing 0.3% salicylic acid-2-ethylhexyl ester. After testing, the coating quality of the ultraviolet shielding layer, the sealing layer, the hydrophobic layer, the ultraviolet absorption layer, etc. in the mica material prepared in this example was basically equivalent to that of the mica material I; its ultraviolet transmittance was about 9.90%, the SPF value was about 36, and the water contact angle was about 141°. Embodiment 21

[0077] Example 1 was repeated, except that the coating reaction time of each coating layer was adjusted with the goal of achieving a coating mass of the ultraviolet absorbing layer of 4% of the total mass of the finished mica material and keeping the mass proportion of other coating layers unchanged; after testing, in the mica material prepared in this example, the coating mass of the ultraviolet shielding layer was approximately 26.2%, the coating mass of the sealing layer was approximately 0.50%, the coating mass of the hydrophobic layer was approximately 4.0%, and the coating mass of the ultraviolet absorbing layer was approximately 3.9%; its ultraviolet transmittance was approximately 0.43%, the SPF value was greater than 50, and the water contact angle was approximately 141°. Embodiment 22

[0078] Example 1 was repeated, except that the coating reaction time of each coating layer was adjusted with the goal of achieving a coating mass of the ultraviolet absorption layer of 2% of the total mass of the finished mica material and the mass proportion of other coating layers remaining unchanged; after testing, in the mica material prepared in this embodiment, the coating mass of the ultraviolet shielding layer was approximately 26.1%, the coating mass of the sealing layer was approximately 0.50%, the coating mass of the hydrophobic layer was approximately 4.0%, and the coating mass of the ultraviolet absorption layer was approximately 2.1%; its ultraviolet transmittance was approximately 4.05%, the SPF fishtail was 48, and the water contact angle was approximately 141°.

[0079] Comparative Example 1 Example 1 was repeated, except that the coating process of the ultraviolet shielding layer was not carried out, and the mass proportion of other coating layers was controlled unchanged, and the coating reaction time of other coating layers was adjusted; after testing, in the mica material prepared by this comparative example, the coating mass of the ultraviolet shielding layer was 0%, the coating mass of the sealing layer was about 0.50%, the coating mass of the hydrophobic layer was about 4.0%, and the coating mass of the ultraviolet absorption layer was about 3.1%; its ultraviolet transmittance was about 9.46%, the SPF value was about 36, and the water contact angle was about 141°.

[0080] Comparative Example 2 Example 1 was repeated, except that the coating process of the sealing layer was not carried out, and the mass proportion of other coating layers was kept unchanged, and the coating reaction time of other coating layers was adjusted; after testing, in the mica material prepared by this comparative example, the coating mass of the UV shielding layer was about 26.2%, the coating mass of the sealing layer was 0%, the coating mass of the hydrophobic layer was about 4.2%, and the coating mass of the UV absorption layer was about 3.2%; its UV transmittance was about 1.01%, the SPF value was greater than 50, and the water contact angle was about 141°.

[0081] Comparative Example 3 Example 1 was repeated, except that the coating process of the ultraviolet absorbing layer was not carried out, and the mass proportion of other coating layers was controlled unchanged, and the coating reaction time of other coating layers was adjusted; after testing, in the mica material prepared by this comparative example, the coating mass of the ultraviolet shielding layer was about 26.1%, the coating mass of the sealing layer was about 0.50%, the coating mass of the hydrophobic layer was about 3.0%, and the coating mass of the ultraviolet absorbing layer was 0%; its ultraviolet transmittance was about 11.3%, SPF was about 28, and the water contact angle was about 141°.

Claims

1. A titanium-free UV-proof mica material, characterized in that: The anti-ultraviolet mica material comprises a mica substrate, an ultraviolet shielding layer coated on the surface of the substrate, a sealing layer coated on the surface of the ultraviolet shielding layer, a hydrophobic layer optionally coated on the surface of the sealing layer, and an ultraviolet absorbing layer coated on the outermost layer; The ultraviolet shielding layer is an oxide layer composed of one or more of zinc oxide, zirconium oxide, silicon dioxide, and magnesium oxide (preferably zinc oxide and / or zirconium oxide); The sealing layer is an oxide layer composed of one or both of aluminum oxide and cerium oxide (preferably cerium oxide); The hydrophobic layer is an organosilane layer; The ultraviolet absorption layer is an organic layer composed of aromatic compounds containing carbonyl groups and having a conjugated structure.

2. The anti-ultraviolet mica material according to claim 1, characterized in that: The aromatic compound containing a carbonyl group and having a conjugated structure is selected from one or more of butyl methoxydibenzoylmethane, bis-ethylhexyloxyphenol methoxyphenyl triazine, polysilicone-15, 2-cyano-3,3-diphenylacrylate-2-ethylhexyl ester, 4-methoxycinnamic acid ethylhexyl ester, 2-hydroxy-4-methoxybenzophenone, and salicylic acid-2-ethylhexyl ester.

3. The anti-ultraviolet mica material according to claim 1 or 2, characterized in that: The organosilane is one or more of polydimethylsiloxane alcohol, n-octyl triethoxysilane, aminopropyl triethoxysilane, stearic acid, palmitic acid, and myristic acid, preferably one or more of aminopropyl triethoxysilane, stearic acid, and n-octyl triethoxysilane.

4. The anti-ultraviolet mica material according to any one of claims 1 to 3, characterized in that: The thickness of the ultraviolet shielding layer is such that its mass is 1-50%, preferably 10-40%, more preferably 20-36% of the total mass of the finished material; and / or The thickness of the sealing layer is such that its mass is 0.1-2%, preferably 0.2-1.8%, more preferably 0.3-1.5% of the total mass of the finished material; and / or The thickness of the hydrophobic layer is such that its mass is 0-5%, preferably 0.4-4%, more preferably 0.6-3.5% of the total mass of the finished material; and / or The thickness of the ultraviolet absorption layer is such that its mass is 0-10% of the total mass of the finished material, preferably 1-8%, more preferably 1-5%; Preferably, the thickness of the sealing layer does not exceed 20% of the thickness of the UV shielding layer, and preferably does not exceed 15% of the thickness of the UV shielding layer.

5. A method for preparing a titanium-free UV-proof mica material or a method for preparing a titanium-free UV-proof mica material as claimed in any one of claims 1 to 4, characterized in that: The method comprises the following steps: 1) dispersing a mica substrate in water to obtain a mica suspension, heating the mica suspension, adding a solution containing ultraviolet shielding agent ions thereto and stirring the suspension for reaction, and after the reaction is completed, calcining the fixed product to obtain product A; 2) dispersing product A in water to obtain suspension A, heating suspension A, adding a solution containing blocking agent ions thereto and stirring to react, and the fixed product obtained after the reaction is completed is product B; 3) placing product B in a container, then adding a solution containing a hydrophobic agent and mixing evenly to obtain a mixture, heating the mixture to perform a curing reaction and completely volatilize the solvent, and obtaining product C after the reaction is completed; 4) dispersing the product B or product C in a solution containing an ultraviolet absorber to obtain a suspension C, concentrating the suspension C and performing low-temperature and reduced-pressure drying treatment to obtain a titanium-free ultraviolet-resistant mica material.

6. The method according to claim 5, characterized in that: In step 1), the solution containing the UV shielding agent ions is Zn 2+ 、Zr 4+ 、SiO3 2- Mg 2+ One or more salt solutions, preferably containing zinc chloride, zinc nitrate, zinc sulfate, zirconium tetrachloride, zirconium sulfate, sodium silicate, potassium silicate, sodium metasilicate, potassium metasilicate, magnesium chloride, magnesium sulfate or one or more salt solutions; preferably, the concentration of the solution containing the ultraviolet shielding agent ions is 0.5-2 mol / L; and / or In step 1), the solid concentration in the mica suspension is 5-15%, preferably 8-12%; and / or In step 1), the mica suspension is heated to 50-75° C., preferably 55-70° C.; preferably, the pH value during the stirring reaction is controlled to be 6.5-7.5, preferably 6.8-7.2; and / or In step 1), the calcination temperature is 500-1200° C., preferably 600-750° C.; the calcination time is 0.1-3 h, preferably 0.3-2 h.

7. The method according to claim 5 or 6, characterized in that: In step 2), the solution containing the blocking agent ions is Al 3+ and / or Ce 4+ A salt solution, preferably a salt solution containing one or more of aluminum chloride, aluminum nitrate, aluminum sulfate, and cerium nitrate; preferably, the concentration of the solution containing the blocking agent ions is 0.5 to 1 mol / L; and / or In step 2), the solid concentration in the suspension A is 5-12%, preferably 7-10%; and / or In step 2), the heating of the suspension A specifically comprises: heating the mica suspension to 60-90° C., preferably 70-85° C.; preferably, after heating, the pH of the suspension A is controlled to be 6-8, preferably 6.5-7.

5.

8. The method according to any one of claims 5 to 7, characterized in that: In step 3), the solution containing the hydrophobic agent is an organic solution containing one or more of polydimethylsiloxane, n-octyltriethoxysilane, aminopropyltriethoxysilane, stearic acid, palmitic acid, and myristic acid; the organic solvent is one or more of ethyl acetate, ethanol, water, citric acid, acetic acid, oxalic acid, and hydrochloric acid; preferably, the mass concentration of the solution containing the hydrophobic agent is 5 to 50%, preferably 8 to 45%; and / or In step 3), the solution containing the hydrophobic agent is added by atomization spraying; and / or In step 3), the mixture is heated for reaction. Specifically, the mixture is heated to 100-140° C. and baked for 4-12 hours, preferably heated to 100-120° C. and baked for 5-10 hours, under stirring.

9. The method according to any one of claims 5 to 8, characterized in that: In step 4), the solution containing the ultraviolet absorber is an organic solution containing one or more of butyl methoxydibenzoylmethane, bis-ethylhexyloxyphenol methoxyphenyl triazine, polysilicone-15, 2-cyano-3,3-diphenylacrylate-2-ethylhexyl ester, 4-methoxycinnamic acid ethylhexyl ester, 2-hydroxy-4-methoxybenzophenone, and salicylic acid-2-ethylhexyl ester; the organic solvent is one or more of petroleum ether, ethyl acetate, ethanol, isopropanol, and water; preferably, the mass concentration of the solution containing the ultraviolet absorber is 0-10%, preferably 0-2%; and / or In step 4), the solid-liquid mass ratio of the intermediate product B or product C to the solution containing the ultraviolet absorber is 1:4-12, preferably 1:6-10; and / or In step 4), the suspension C is concentrated and dried at low temperature and reduced pressure by first heating the suspension C to 40-60° C. under vacuum conditions for evaporation concentration (preferably heating to 45-55° C. for evaporation concentration); and then continuing to heat until the solvent is completely volatilized.

10. Use of a titanium-free UV-proof mica material or the titanium-free UV-proof mica material as claimed in any one of claims 1 to 4 or the titanium-free UV-proof mica material prepared by the method as claimed in any one of claims 5 to 9, characterized in that: The titanium-free UV-proof mica material is used to prepare cosmetics; preferably, the titanium-free UV-proof mica material is used to prepare one or more of lip gloss, eye shadow, pressed powder, nail polish, lotion, face cream, shampoo, cleansing cream, and handmade soap.